Improved Stereochemical Analysis of Conformationally Flexible Diamines by Binding to a Bisporphyrin Molecular Clip. Issue 43 (11th September 2013) - Norrehed, Sara; Johansson, Henrik; Grennberg, Helena; Gogoll, Adolf
Abstract The relative stereochemistry of acyclic diamines with several stereogenic centers has been analyzed by NMR spectroscopy in combination with conformational deconvolution. Binding to a bisporphyrin molecular clip improves the stereochemical assignment significantly. The diamines were synthesized from inexpensive sugar alcohols, and their stable hydrochlorides were quantitatively converted into free bases by treatment with ion‐exchange resin.